Effects of Prices, Product Quality, and Halal Labels on Repurchase Interest of Wardah at Avon Stores Purwoharjo Banyuwangi - Imam Abrori; Tri Agustin; M. Rijalus Sholihin (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Research on prices, product quality, and halal labels on the repurchase interest of Wardah products. The research objective was to see and analyze the effect of price (X1), product quality (X2), halal label (X3) on repurchase interest (Y) at Wardah outlets at Avon Cosmetics Banyuwangi. Data were collected by means of observation, interviews and questionnaires to 60 respondents with a purposive technique using accidental sampling, which aims to see the respondents' perceptions of each variable. The analysis used includes instrument test, multiple linear regression analysis, classical assumption test, and hypothesis testing. The results of analysis using regression can be seen that the variable price (X1), product quality (X2), halal label (X3), all have a positive effect on repurchase interest (Y). From the test, the results obtained from the price (0.012), product quality (0.001), halal label (0.000), all have a positive effect on the repurchase interest of Wardah products. The third variable has an effect of 73.4% and the remaining 26.5%.